Consumers' willingness to adopt genetically modified foods. Issue 3 (13th November 2020) - Fozouni Ardekani, Zahra; Akbari, Morteza; Pino, Giovanni; Zúñiga, Miguel Ángel; Azadi, Hossein
Abstract : Purpose: This study investigates consumers' willingness to adopt genetically modified foods (GM) and the role of innovation and behavioral determinants. Design/methodology/approach: A new integrated model that expands the Health Belief Model (HBM) into the Innovation Diffusion Theory (IDT) was developed and examined. A total of 241 consumers were selected from the capital of Iran, Tehran, through a multistage random sampling. The data were analyzed using SEM-PLS modeling. Findings: The extended HBM model was able to predict about 84% of the variance changes in consumers' willingness to adopt GM foods. The effects of net benefit and perceived compatibility on the willingness were also significant. In addition, the mediating effect of compatibility on the relationship between net benefit/self-efficacy and willingness to adopt GM foods was also significant. Originality/value: This study contributes to the literature by developing the HBM into the IDT to assess consumers' willingness to adopt GM foods.